An Economic Analysis of the Effect of a Government Institution’s Purchase Quantities on the Wheat Market in Turkey - Konyalı, S.; Unakıtan, G.; Gaytancıoglu, O. (2012)
Wheat is under cultivation in Turkey over an area of approximately 9.3 million ha, which on the average, produces 20 million tons of wheat annually. Wheat production occupies approximately 35% of the agricultural land in Turkey. In this study, the interactions between wheat production, wheat import and export quantities, domestic and world wheat prices, and purchases of wheat by the most important stocker of wheat in Turkey, the Soil Products Office (SPO), were examined using the Vector Autoregressive Regression (VAR) model. The data used in this research covered the period 1961– 2005. Price variables were realized with the Producer Price Index (PPI). Based on the results of variance decomposition and the average of a 10-yr period, 30% of the variability in SPO purchases was affected by itself. Wheat production was affected by its variability at the rate of 63.76%, while 52.72% of the variability in domestic prices was explained by itself.
Keywords: Agricultural economics; Wheat--Yields.